Smart Glasses Using Arduino Nano - Gagana V, Pooja K, Chaitra Nayak J, Niharika B C , M Rahul Kumar Reddy (International Journal of Advanced Science and Technology, 2020)
Smart glass is a futuristic device. It is one of the wearable devices that is capable of handling wide range of activities that an ordinary human alone cannot do in quick time. It is a head mounted device that shows data in front of one eye of the user, which enables the user to see the display independently of their position and orientation. The user can interact with real world and digital world simultaneously. The glass is smartly constructed with miniature frame. OLED display and lens are used for the glass frame’s desired reflection. Smart glass easily fits the person and allow the user to experience virtual reality.